De-centering state making comparative and international perspectives - edited by Jens Bartelson (Cheltenham Edward Elgar Publishing, 2018)
State making has long been regarded as a European development, both historically and geographically. In this innovative book, the authors add fresh insights into the nature and causes of state making by de-centering this Eurocentric viewpoint through simultaneous changes of conceptual, theoretical and empirical focus.
Includes bibliographical references and index
Keywords: POLITICAL SCIENCE -- International Relations -- General; Political geography; International relations; Comparative government; Historical sociology; POLITICAL SCIENCE / Government / International; POLITICAL SCIENCE / International Relations / General; Comparative government; Historical sociology